Development and performance testing of a small, multi-bladed wind turbine. Issue 1 (February 2020) - Sant, Tonio; Farrugia, Robert N; Muscat, Martin; Caruana, Cedric; Axisa, Redeemer; Borg, Albert; Cassar, Cecille M; Cassar, Josianne; Cordina, Christian; Farrugia, Adrian; Schembri, Steven
This article presents selected results from the development process of a small, prototype multi-bladed wind turbine designed to replace the American western-style, wind-driven water pumps still encountered in the Maltese rural landscape. The main focus of this article is on the rotor design, fabrication and system assembly, as well as on the results of the first open field tests. While the new design proves that the new machine is capable of aesthetically representing the windmills of old, preliminary findings indicate that it is also capable of meeting its predicted performance characteristics in a satisfactory manner, albeit subject to the installation site's specific wind climatology.